Theoretical Bases of Forming Foreign Language Communicative Competence as a Component of Professional Competency of the Future Teacher of Foreign Language - Inna Yashchuk (Pedagogical Discourse, 2017)
The article deals with the approaches of Ukrainian and foreign researchers to define the content and structure of notions «competence», «communicative competence», «professional competence». A brief description is given to the concept of the notion «foreign language communicative competence» as a key one in the study. The comparison of European and Ukrainian variants of the component composition of foreign language communicative competence shows that the structure of communicative competence is not complete and requires improvements. The article shows the necessity of forming and improving foreign language communicative competence in a combination of its components: lingual, speech, socio-cultural, compensatory, educational and cognitive competences. The state educational standards for higher tducational schools initiates the need to train specialists who are ready to develop foreign language communicative competence of students. Teacher training requires examining of different approaches to the definition, content and structure of foreign language communicative competence, analyzing requirements and creating conditions promoting the formation of the communicative competence of pupils.Key words: competence, communicative competence, foreign language communicative competence, professional competence, future teachers of foreign languages.